Práticas de letramento na Terra Indígena de Dourados/MS: um olhar sobre a circulação dos discursos - Stefanello, Paulo Gerson Rodrigues (Universidade Federal de São Carlos, 2018)
The appropriation of written language as a communication technology, especially when referring to intercultural dialogue involving indigenous people, is a phenomenon that has consolidated throughout the social and historical processes in Brazilian reality. For the purposes of cultural preservation and maintenance, the writing ability showed to be essential for many traditional people who found themselves politically, geographically and culturally inserted in the surrounding society, but who became socially underrepresented. In this context, I situate this thesis in the context of the Indigenous Reserve Francisco Horta Barbosa, in Dourados/MS, in the Brazilian Midwest region, where the non-governmental organization Ação de Jovens Indígenas (AJI) takes place, and which I understand as an agency of literacy (STREET, 1984, 2006; HEATH, 1983; KLEIMAN, 1995; KLEIMAN and ASSIS, 2016) and of translation (LOTMAN, 1996, 1998), that promotes a series of social practices among young people of the local ethnic groups Guarani and Terena. In addition to mastering written language, this group had to master the technology-related knowledge required for the construction and maintenance of a website that, among other functions, serves as a bridge to contact with other societies through the internet, making it possible to outsource their way of life and the facts linked to it. The virtual environment in question is taken in this work as a cultural artifact (BARTLETT, 2007) composed of several texts which can, through the postulates of the Critical Discourse Analysis (FAIRCLOUGH, 2016) and, in parallel with the indicial paradigm (GINZBURG, 1989), help to understand how the semiotic system of the cultural dialogue is, by admitting, considering, the semiosphere theory (LOTMAN, 1996, 1998, MACHADO, 2003, 2007) and its translational character. Thus, the analysis of some materials produced by the AJI and made available in its website denotes the central aim of this research, which is to understand its circulation from the discoursive and social practices, adopting an interdisciplinary theoreticalmethodological course, guided with inscription in the Applied Linguistics.
Literacy practices in the Indigenous Land of Dourados/MS: a look at the discourse circulation
Keywords: Letramentos; Prática social; Semiosfera; Tradução; AJI; Literacies; Semiosphere; Social practice; Translation; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA